REKONSTRUKSI BIOGRAFI DAN KARYA KYAI IMAM BUKHORI JATINOM-BLITAR - Fuad Ngainul Yaqin; Anis Tilawati; Moch. Abdul Rohman; Faza Nur Aida Putri Aulia (Center for the Research and the Communicator Service of IAI Hasanuddin Pare-Kediri, 2024)
Ancient manuscripts are a highly valuable cultural heritage. As one of the primary sources of research, of course we must appreciate its presence because it contributes to the development of the treasures of science and technology. Research that uses ancient manuscripts as the object of study has been increasingly carried out by scholars recently, both from within and outside the country. Speaking about Mbah Kyai Imam Bukhori Jatinom-Blitar, he cannot be separated from the long history that he has carved with his works. As far as the data that researchers can get, Mbah Kyai Imam Bukhori has many manuscripts that until now not many people know about. Because many have not been identified, let alone codified. This is a concern in itself and a solution must be found immediately, so that future generations can also enjoy the nation's cultural heritage. Remembering that manuscripts are a shortcut to bring the present closer to the past in a genuine way. The research methodology used is philological research, data collection tools by carrying out observations and recording. Philological research work steps include: determining research targets, manuscript inventory, observation, manuscript description, manuscript transliteration, text editing and translation, as well as manuscript content summary and content analysis